2008
DOI: 10.1080/00222930701860124
|View full text |Cite
|
Sign up to set email alerts
|

Amphipoda from marine caves of Hong Kong Island

Abstract: A collection of 32 amphipod species from submarine cave habitats and control sites to the east of Hong Kong Island was made during a joint NHM/SWIMS expedition in October 2002. Three families (Caprellidae, Endevouridae and Kamakidae), nine genera (Monoliropus, Caprella, Paraloiloi, Leptocheirus, Microjassa, Cerapus, Listriella, Ensayara and Birubius) and 12 species (Monoliropus concavimanus sp. nov.; Caprella aff. penantis; Elasmopus sp. A; Ptilohyale aff. barbicornis; Cerapus sp. A; Paraloiloi sp. A; Ensayara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Though many ecological and taxonomical studies have been conducted in marine caves, their soft-bottom communities have often been overlooked. The sediment assemblages inhabiting marine caves often show a distinctive species composition and usually hold many new and endemic species (Bamber et al 2008;Horton 2008). Within them, crustaceans (and mainly amphipods) are the dominant taxa in both abundance and number of individuals (NavarroBarranco et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Though many ecological and taxonomical studies have been conducted in marine caves, their soft-bottom communities have often been overlooked. The sediment assemblages inhabiting marine caves often show a distinctive species composition and usually hold many new and endemic species (Bamber et al 2008;Horton 2008). Within them, crustaceans (and mainly amphipods) are the dominant taxa in both abundance and number of individuals (NavarroBarranco et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, >10 species of gammarideans were identified, but only one, Maera pacifica Schellenberg, 1938, has been reported from Hong Kong previously (Moore, 1990). Although knowledge of Hong Kong gammaridean amphipods (Hirayama, 1990a, b, 1991; Moore, 1990, Lowry, 2000; Horton, 2008) is fragmentary, resulting in the novel species recorded from this study, the dramatic difference between the benthic community and the trap samples supports the contention of Shulenberger & Hessler (1974) and Nishida et al (1999) that trapping with bait is an efficient means of collecting dispersed, swimming and elusive hyperbenthic species obtained only rarely by other methods.…”
Section: Discussionmentioning
confidence: 99%
“…However its occurrences in shallow mangrove sediments were unknown until now and requires further investigation. The barcoded Protohyale honoluluensis (Schellenberg, 1938) in this study was known to occur in the Hong Kong Island marine caves of (Horton, 2008).…”
Section: Species Composition and History Of Its Occurrencesmentioning
confidence: 93%